MENGUKUR KETERLIBATAN SISWA DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Mega Rezky (YAYASAN CENDEKIA CITRA GEMILANG, 2024)
At every stage of education, mathematics is a subject that is always required to be studied. It is also called exact science because mathematics cannot be tested and is certain because of its results and formulas. Teachers' lack of enthusiasm for the material when preparing classes and acting as teachers in the learning process will encourage them to create new methods and models to increase students' interest and motivation. Therefore, theories in learning mathematics combine various approaches and principles to help students understand mathematical concepts better. Teaching and learning activities often show students are not involved, not active, and do not take the initiative. Teacher statements usually only move in one direction, they view students as recipients, note-takers, and reminders. Based on what has been widely observed in efforts to increase student involvement in their education, it is very important to review qualitative understanding of events that are happening at school or make them the center of attention to then determine how students behave.